Analisis Kebutuhan Traffic Light Simpang Lima Tak Bersinyal (Studi Kasus: Jl. Akordian Selatan-Jl. Saxophone-Jl.Akordion-Jl. Simpang Akordion-Jl. Candi Panggung, Kota Malang) - Viktor Bili Bulu; Yurnalisdel Yurnalisdel; Rifky Aldila Primasworo (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The five-way intersection without traffic signals at the junction of Jalan Akordion Selatan, Jalan Saxophone, Jalan Akordion, Jalan Simpang Akordion, and Jalan Candi Panggung Barat experiences congestion due to the large number of vehicles. To estimate traffic flow conditions over the next five years, evaluate intersection performance, and determine whether traffic lights are needed, this study was conducted. The 2023 Indonesian Road Capacity Guidelines (PKJI) were used as the basis for analysis after a primary survey was conducted by recording vehicle volume for seven days between 06:00 and 22:00. At the southern approach, the degree of saturation (DS) was 0.202 (LOS B), west 0.489 (LOS C), north 0.201 (LOS B), and east 0.599 (LOS C), according to the 2025 observation findings. Several approaches are at LOS D (congested) and approaching the saturation limit (DS > 0.85), according to five-year predictions, which show an increase in DS to 0.258 (south), 0.625 (west), 0.256 (north), and 0.764 (east), with a total flow of 6,861 pcu/hour. An ideal signal cycle of 85 seconds is recommended by calculations using the Webster technique to regulate traffic flow. These findings indicate that the installation of traffic signals is crucial to improve intersection functionality, reduce delays, and facilitate better traffic flow.